Electrospun 1D and 2D Carbon and Polyvinylidene Fluoride (PVDF) Piezoelectric Nanocomposites. (30th April 2022) - Song, Hang; Song, Wenhui; Song, Jin-hua; Torrejon, Virginia Martin; Xia, Qinxiang
Abstract : Piezoelectric nanocomposite fibrous membranes consisting of polymer polyvinylidene fluoride (PVDF) as matrix and incorporating 1D carbon nanotubes (CNTs) and 2D graphene oxide (GO) were prepared using an electrospinning process. The influence of the filler type, loading, and dispersion status on the total PVDF crystallinity (X c ); the relative fraction of the β phase (piezoelectric phase) in crystalline PVDF (F β ); the volume fraction of β phase in the samples (v β ); and the piezoelectric coefficient d 33 were investigated. The v β is used to assess the formation of β phase for the first time, which considered the combined influence of fillers on X c and F β, and is more practical than other investigations using only F β for the assessment. The inclusion of all types of carbon fillers had resulted in a considerable reduction in the X c compared with the neat PVDF, and the X c decreased with the CNT loading while increased with the GO loading. The addition of CNT and GO had also reduced the F β compared with the neat PVDF, and F β increased with CNT loading while decreased as GO loading increased. The v β is significantly reduced by the addition of CNT and GO, while v β decreases with CNT and GO loading increases. Since the calculation of v β has considered the combined influence of fillers on X c and F β, both of which were reduced by incorporating CNT and GO, the reduction of v β was expected. The v β of the PVDF/CNT composites were higher than that of the PVDF/GO composites. Although it is generally anticipated that d 33 increases with v β, it is observed that in the presence of CNT, d 33 is dominated by the increase in electric conductivity of the composites during and after the electrospinning process, giving rise to transport of charges, produced by β crystals within the fiber to the surface of the sample. In addition, the 1D CNTs may have promoted the orientation of β crystals in the d 33 direction, therefore, enhancing the d 33 of the composites despite the hindrance of the β -phase formation (i.e., the reduction of v β ). Adding CNTs can also improve piezoelectricity through interfacial polarization, which increases the dielectric constant of composite (mobile charges within CNTs facilitate composite polarization). CNT loadings higher than 0.01 wt.% are sufficient to outperform the neat PVDF, and d 33 becomes 59.7% higher than the neat PVDF at 0.03 wt.% loading, but only GO loadings of 0.5 wt.% achieved comparable d 33 to the neat PVDF; further increase in GO loading had resulted in a decline in d 33 . The low conductivity of GO, the influence of flocculation, and the lower aspect ratio compared with CNT may result in lower electron transfer and less orientation of the β -phase polycrystalline. The d 33 of the PVDF/CNT composites is higher than that of the PVDF/GO composites despite much higher loading of GO. This study aims to contribute to the development of PVDF nanocomposites in piezoelectric energy harvesting applications (e.g., self-powered biosensors and wireless sensor networks).